TRANSFORMASI PENEGAKAN DUE PROCESS OF LAW DALAM TAHAPAN PENYIDIKAN DI INDONESIA: ANTARA PERLINDUNGAN HAK TERSANGKA DAN EFEKTIVITAS PENEGAKAN HUKUM - Kurdi; Adery Ardhan; Teuku Ahmad Dadek (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the legal problem of the transformation of due process of law at the investigation stage in Indonesia, where the protection of suspects’ rights continues to conflict with the effectiveness of law enforcement. Normatively, the Criminal Procedure Code (KUHAP) adopts the Due Process Model, yet in practice the Crime Control Model remains dominant, creating a gap between das sollen and das sein. This research employs a normative legal research method through statutory, doctrinal, and case analysis to assess suspects’ rights and oversight mechanisms during investigations. The findings reveal that the right to legal assistance under Articles 54 and 56 of the KUHAP is still weakly implemented, contributing to the persistence of torture to obtain confessions. Internal and external oversight mechanisms have also proven suboptimal. A significant shift emerges from Constitutional Court Decision No. 21/PUU-XII/2014, which expands pretrial review to include suspect determination, searches, and seizures. Normatively, the study concludes that strengthening due process of law requires legislative reform by institutionalizing the Commissioner Judge as a proactive judicial supervisor.